2000
DOI: 10.1034/j.1600-0625.2000.009005341.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression patterns distinguish HIV associated skin diseases

Abstract: AIDS is known to cause a shift of cytokines in the periphery. However, predominant cytokines in skin of patients with HIV-associated skin diseases have not been clearly defined. We hypothesized that there are distinct cytokine profiles that distinguish among the different clinical manifestations of AIDS-related skin diseases. To test this hypothesis, lesional and non-lesional skin was biopsied from 53 HIV+ patients with Kaposi's sarcoma (KS), psoriasis, and pruritus due to eosinophilic folliculitis, and from H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…Apart from the secretion of IL-31, hBDs and LL-37 also enhanced the release of numerous cytokines, including IL-2, IL-4, IL-6, IL-8, GM-CSF, and TNF-a, which are known to play a role in the elicitation of itching (52)(53)(54)(55)(56)(57). However, several experimental studies have suggested an indirect pruritogenic effect of above cytokines via other mediators (55,58).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the secretion of IL-31, hBDs and LL-37 also enhanced the release of numerous cytokines, including IL-2, IL-4, IL-6, IL-8, GM-CSF, and TNF-a, which are known to play a role in the elicitation of itching (52)(53)(54)(55)(56)(57). However, several experimental studies have suggested an indirect pruritogenic effect of above cytokines via other mediators (55,58).…”
Section: Discussionmentioning
confidence: 99%
“…Az immunológiai funckiók HIV okozta folyamatos romlása következtében fellépő opportunista fertőzések és fokozott karcinogenezis jól ismert folyamatok, azonban a primer HIV-bőrtünetek közé sorolt, nagyrészt klasszikus bőrbetegségek (például psoriasis vulgaris, atopiás dermatitis, seborrhoeás dermatitis) atípusos és terápiarezisztens megjelenése HIV-fertőzötteken intenzív kutatások tárgya. A bőrtünetek kialakulásában -az epidermisben jelen levő antigénpre-zentáló sejtek számbeli és funkcióbeli csökkenése mellett -szerepet tulajdonítanak a CD4-lymphocyta-szám csök-kenésének, a HIV okozta komplex immundiszreguláció-nak, de a szuperantigén-és citokinhatásoknak is [8,9].…”
Section: Hiv-asszociált Bőrtünetekunclassified
“…A klinikai különbségek hátterében több mechanizmust is feltételeznek. A HIV mint cutan gyulladást provokáló ágens és a HIV okozta immundiszreguláció, ami módosítja a cutan citokinmiliőt, magyarázhatja a psoriasis súlyosabb lefolyását [9,15]. Az utób-bi időben a fi gyelem a retrovírusok autoimmun és autoinfl ammatorikus betegségeket kiváltó tulajdonsága felé fordult.…”
Section: Psoriasis Vulgarisunclassified
“…Several reviews reported the clinical, histological, and immunohistochemical findings that distinguish HIV-PPE from HIV-EF. [8][9][10][11][12][13][14] The impact of histopathological differentiation on therapy choice was proposed by Holmes, Martins, and Horn, 15 but differential diagnosis criteria distinguishing between these two entities have not been established.…”
Section: Introductionmentioning
confidence: 99%